Degradability of composites, prepared from ethylene-propylene copolymer and jute fiber under accelerated aging and biotic environments - Kumar, AP; Singh, RP; Sarwade, BD (Materials Chemistry and Physics, 2005)
The utilization of natural fiber as reinforcement for the thermoplastic composites is growing not only for ecological concern but also for wide range of applications. In the present article, three types of composites were prepared by melt mixing of ethyl ene-propylene (EP) copolymer and (i) 3% NaOH treated jute fiber, (ii) 17.5% NaOH treated jute fiber and (iii) commercial microcrystalline cellulose powder using maleated EP copolymer as compatibilizer. The obtained composites were characterized by Fourier transform infrared spectroscopy (FTIR), Thermal gravimetric analysis (TGA) and microscopic measurements. The durability of the composites was evaluated under polychromatic irradiation (λ &GE; 290 nm) and composting condition for different time intervals. It was found that the treatments on the natural fiber have influenced the service life of the end product. Composites made from microcrystalline cellulose showed better mechanical properties as well as photo-resistance. The specimen containing 3% NaOH treated fiber exhibited relatively lowest photo-resistance and biosusceptibility. It was found that the composites were less durable under both abiotic and biotic conditions in comparison of the neat polymer matrix. © 2005 Elsevier B.V. All rights reserved.
Keywords: accelerated aging and composting; composites; ethylene-propylene (EP) copolymers; jute fibers; mechanical properties; microcystalline cellulose powder

Durability of natural fiber-reinforced composites of ethylene-propylene copolymer under accelerated weathering and composting conditions - Kumar, A. P.; Depan, Dilip; Singh, R. P. (Journal of Thermoplastic Composite Materials, 2005)
Three types of composites are prepared by the melt mixing of ethylene-propylene copolymer (EPC) with (i) 3 % NaOH-treated jute fiber, (ii) 17.5 % NaOH-treated jute fiber, and (iii) commercial microcrystal line cellulose powder using maleated EPC as compatibilizer. The composites obtained are characterized by FTIR and microscopic measurements. Their mechanical properties are measured using a UTM (Instron model 4204). The durability of the composites is evaluated in an irradiation chamber with UV radiation of wavelength lambda >= 290 mn and composting conditions at different time intervals. The composites made from microcrystalline cellulose show superior mechanical properties, biodisintegrability, as well as photoresistance whereas the specimen containing 3% NaOH-treated fiber exhibited the lowest photoresistance. Increasing the quantity of maleated EP (MEP) in the composition decreases photostability. Neat EPC has been found to be highly stable than all the composites with increasing UV irradiation. It has been found that the composites are less durable under both abiotic and biotic conditions in comparison to the neat polymer.
Keywords: compatibilization; composites; jute fiber; mechanical properties; Microcrystalline cellulose; photodegradation and composting

Influence of organic modification on mechanical properties of melt processed intercalated poly(methyl methacrylate)-organoclay nanocomposites - Tiwari, Rajkiran R.; Natarajan, Upendra (Journal of Applied Polymer Science, 2007)
The influence of organic modifiers on intercalation extent, structure, thermal and mechanical properties of poly(methyl methacrylate) (PMMA)-clay nanocomposites were studied. Two different organic modifiers with varying hydrophobicity (single tallow versus ditallow) were investigated. The nanocomposites were prepared from melt processing method and characterized using wide angle X-ray diffraction, transmission electron microscopy, thermogravimetric analysis, differential scanning calorimetry (DSC), and tensile tests. Mechanical properties such as tensile modulus (E), break stress (sigma(brk)), and 0% break strain (epsilon(brk)) were determined for nanocomposites at various clay loadings. Extent of PMMA intercalation is sufficient and in the range 9-15 angstrom depending on organoclay and filler loading. Overall thermal stability of nanocomposites increases by 16-30 degrees C. The enhancement in T-g of nanocomposite is merely by 2-4 degrees C. With increase in clay loading, tensile modulus increases linearly while % break strain decreases. Break stress is found to increase till 4 wt % and further decreases at higher clay loadings. The overall improvement in thermal and mechanical properties was higher for the organoclay containing organic modifier with lower hydrophobicity and single tallow amine chemical structure. (c) 2007 Wiley Periodicals, Inc.
Keywords: mechanical properties; Nanocomposites; organoclay; structure; Thermal properties

Development of nanofibrous morphology in LDPE/LLDPE/PP blends and its effect on mechanical properties of blend films - Sonawane, Pradip S.; Radhakrishnan, S.; Bhangale, J. A.; Gadhavi, A. L.; Khare, Anagha (Journal of Applied Polymer Science, 2008)
Nanofibrous morphology has been observed in ternary blends of low density polyethylene (LDPE), linear low density polyethylene (LLDPE), and isotactic polypropylene (PP) when these were melt-extruded via slit die followed by hot stretching. The morphology was dependent on the concentration of the component polymers in ternary blend LDPE/LLDPE/PP. The films were characterized by wide angle X-ray diffraction (XRD), scanning electron microscopy (SEM), and testing of mechanical properties. The XRD patterns reveal that the P phase of PP is obtained in the as-stretched nanofibrillar composites, whose concentration decreases with the increase of LLDPE concentration. The presence of PP nanofibrils shows significant nucleation ability for crystallization of LDPE/LLDPE blend. The SEM observations of etched samples show an isotropic blend of LDPE and LLDPE reinforced with more or less randomly distributed and well-defined nanofibrils of PP, which were generated in situ. The tensile modulus and strength of LDPE/LLDPE/PP blends were significantly enhanced in the machine direction than in the transverse direction with increasing LLDPE concentration. The ultimate elongation increased with increasing LLDPE concentration, and there was a critical LLDPE concentration above which it increased considerably. There was a dramatic increase in the falling dart impact strength for films obtained by blow extrusion of these blends. These impressive mechanical properties of extruded samples can be explained on the basis of the formation of PP nanofibrils with high aspect ratio (at least 10), which imparted reinforcement to the LDPE/LLDPE blend. (C) 2007 Wiley Periodicals, Inc.
Keywords: linear low density polyethylene; low density polyethylene; mechanical properties; melt-extruded films; nanofibrous morphology; polypropylene; ternary blends

New poly(phenylene oxide)/polystyrene blend nanocomposites with clay: intercalation, thermal and mechanical properties - Tiwari, Rajkiran R.; Khilar, Kartic C.; Natarajan, Upendra (Journal of Applied Polymer Science, 2008)
We present the first study and results on the preparation and characterization of montmorillonite clay filter based polymer blend nanocomposites of the miscible poly(phenylene oxide)/polystyrene blend. Intercalated nanocomposites, prepared by a melt-processing method with 2-6 wt % commercially available organically modified sodium montmorillonite, have been characterized with wide-angle X-ray diffraction, transmission electron microscopy analysis, thermal analysis (thermogravimetric analysis and differential scanning calorimetry), and mechanical tensile tests. We show that nanocomposites can be successfully prepared in a batch mixer at temperatures much below the conditions conventionally used for this blend without organic degradation. Thermal stability is enhanced by nanoscale hybrid formation. The level of intercalation (change in the d-spacing) does not change with the clay loading. Better dispersion of clay in the blend matrix has been observed at a low level of clay content. The nanocomposites show improved tensile modulus (by 31%) in comparison to the blend, whereas the tensile strength (stress at break) and elongation decrease in the presence of the filler with an increase in the clay loading. The Halpin-Tsai model is able to predict the modulus of the nanocomposites in very good agreement with the experimental data. (c) 2008 Wiley Periodicals, Inc.
Keywords: mechanical properties; Nanocomposites; organoclay; poly(phenylene oxide); Polystyrene; Thermal properties

Thermal and mechanical properties of melt processed intercalated poly(methyl methacrylate)-organoclay nanocomposites over a wide range of filler loading - Tiwari, Rajkiran R.; Natarajan, Upendra (Polymer International, 2008)
BACKGROUND: Poly(methyl methacrylate) (PMMA)-organoclay nanocomposites with octadecylammonium, ion-modified montmorillonite, prepared via melt processing, over a wide range of filler loading (2-16 wt%) were investigated in detail. These hybrids were characterized for their dispersion structure, and thermal and mechanical properties, such as tensile modulus (E). break stress (sigma(brk)), percent break strain (epsilon(brk)) and ductility(J), using wide-angle X-ray diffraction, transmission electron microscopy, differential scanning calorimetry (DSC), thermogravimetric analysis (TGA) and tensile and impact tests. RESULTS: Intercalated nanocomposites were formed even in the presence of 16 wt% clay (high loading) in PMMA matrix. PMMA intercalated into the galleries of the organically modified clay, with a change in d-spacing in the range 11-16 angstrom. TGA results showed improved thermal stability of the nanocomposites. The glass transition temperature (T-g) of the nanocomposites, from DSC measurements, was 2-3 degrees C higher than that of PMMA. The ultimate tensile strength and impact strength decreased with increasing clay fraction. Tensile modulus for the nanocomposites increased by a significant amount (113%) at the highest level of clay fraction (16 wt%) studied. CONCLUSION: We show for the first time the formation of intercalated PMMA nanocomposites with alkylammonium-modified clays at high clay loadings (> 15wt%). Tensile modulus increases linearly with clay fraction, and the enhancement in modulus is significant. A linear correlation between tensile strength and strainat-break is shown. Thermal properties are not affected appreciably. Organoclay can be dispersed well even at high clay fractions to form nanocomposites with superior bulk properties of practical interest. (c) 2007 Society of Chemical Industry.
Keywords: impact strength; mechanical properties; Nanocomposites; PMMA; Thermal properties

Effect of gamma-dose rate on crystallinity and morphological changes of gamma-sterilized biomedical polypropylene - Alariqi, Sameh A. S.; Kumar, A. Pratheep; Rao, B. S. M.; Singh, R. P. (Polymer Degradation and Stability, 2009)
The present work is aimed to study the changes in crystallinity and morphology of biomedical polyolefins after gamma-sterilization. The isotactic polypropylene (iPP) films were sterilized by gamma-radiation and the changes were characterized by differential scanning calorimetry (DSC), wide angle X-ray diffraction (WAXD) and atomic force microscopy (AFM) techniques. The effect of dose rate on crystallinity changes also was focused. It was found that crystallinity and morphology significantly changed with gamma-irradiation. There was an increase in crystallinity Lip to 10 kGy accompanied with decrease in viscosity and mechanical properties. The changes in crystallinity mainly depend on gamma-irradiation dose and dose rate. The rise in crystallinity was attributed to chain scission and forming new perfect lamellae. However, the reduction was accompanied by occurrence of gamma- and beta-phases and crosslinking. Possible explanations for transitions in phases are also discussed based on our results. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Crystallinity; Dose rate; Gamma radiation; mechanical properties; Morphology; polypropylene

Novel synthesis of nano-calcium carbonate (CaCO3)/polystyrene (PS) core-shell nanoparticles by atomized microemulsion technique and its effect on properties of polypropylene (PP) composites - Mishra, Satyendra; Chatterjee, Aniruddha; Singh, RajPal (Polymers for Advanced Technologies, 2011)
Calcium carbonate (CaCO3)/polystyrene (PS) nanoparticles (< 100 nm) with core-shell structure were synthesized by atomized microemulsion technique. The polymer chains were anchored onto the surface of nano-CaCO3 through triethoxyvinyl silane (TEVS) as a coupling agent. Ammonium persulfate (APS), sodium dodecyl sulfate (SDS) and n-pentanol were used as initiator, surfactant, and cosurfactant, respectively. Polymerization mechanism of core-shell latex particles was discussed. Encapsulation of nano-CaCO3 by PS was confirmed by using transmission electron microscope (TEM). Grafting percentage of core-shell particles was investigated by Thermogravimetric Analyzer (TGA). Nano-CaCO3/PS core-shell particles were characterized by Fourier transform infrared (FTIR) spectrophotometer and differential scanning calorimeter (DSC). The results of FTIR revealed existence of a strong interaction at the interface of nano-CaCO3 particle and PS, which implies that the polymer chains were successfully grafted onto the surface of nano-CaCO3 particle through the link of the coupling agent. In addition, TGA and DSC results indicated an enhancement of thermal stability of core-shell materials compared with the pure nano-PS. Nano-CaCO3/PS particles were blended with polypropylene (PP) matrix on Brabender Plastograph by melt process with different wt% of loading (i.e. 0.1-1 wt%). The interfacial adhesion between nano-CaCO3 particles and PP matrix was significantly improved when the nano-CaCO3 particles were grafted with PS, which led to increased thermal, rheological, and mechanical properties of (nano-CaCO3/PS)/PP composites. Scanning electron microscope (SEM) and atomic force microscope (AFM) images showed a perfect dispersion of the nano-CaCO3 particles in PP matrix. Copyright (C) 2011 John Wiley & Sons, Ltd.
Keywords: atomized microemulsion; core-shell nanoparticles; mechanical properties; polypropylene (PP); Rheological properties; Thermal properties

Polybenzimidazoles based on 3,3 `-diaminobenzidine and aliphatic dicarboxylic acids: synthesis and evaluation of physicochemical properties toward their applicability as proton exchange and gas separation membrane material - Bhavsar, Rupesh S.; Nahire, Sandip B.; Kale, Mrunali S.; Patil, Shubhangi G.; Aher, Pradnya P.; Bhavsar, Ritesh A.; Kharul, Ulhas K. (Journal of Applied Polymer Science, 2011)
A series of aromatic-aliphatic polybenzimidazoles (PBIs) based on 3,3'-diaminobenzidine (DAB) and aliphatic dicarboxylic acid with incremental -CH2- groups were synthesized. Optimization of synthesis parameters and evaluation of physicochemical properties are requisite for PBI applicability as the proton exchange membrane (PEM) and gas separation membrane materials are reported. It was found that though all these PBIs exhibited high thermal, mechanical, and oxidative stability, effect of added flexibility on physical properties is not monotonous. Membranes were prepared by solution casting as well as phase-inversion method. The later types of membranes exhibited much higher H3PO4 content than its doping achieved in the solution casted membranes. These PBIs possess low hydrogen and helium permeability than that of conventional PBI. This low permeability, along with their excellent oxidative stability indicated that they can be promising PEM materials. Their CO2-sorption analysis revealed that PBI6 based on suberic acid possesses appreciable CO2 sorption. (C) 2010 Wiley Periodicals, Inc. J Appl Polym Sci 120: 1090-1099, 2011
Keywords: Gas permeation; mechanical properties; membranes; oxidative stability; polybenzimidazoles

Mechanical properties of polypropylene blended with esterified and alkylated lignin - Maldhure, Atul V.; Ekhe, J. D.; Deenadayalan, E. (Journal of Applied Polymer Science, 2012)
Lignin does not show miscibility with commercial polyolefins. Therefore, industrial waste lignin was modified in two different ways and subsequently blended with commercial polypropylene (PP) up to 25 wt %. A Brabender electronic plasticorder was used for melt mixing at 190 degrees C. The influence of different modifications on the mechanical properties and processing stability was studied for both polymer blends. The blends of PP and lignin modified (esterified) with maleic anhydride showed less deterioration in the mechanical properties compared to blends of PP and alkylated lignin with dichloroethane. Intermolecular interactions between the PP matrix and modified lignin were concluded on the basis of indicative values derived from various relevant theoretical models to the experimental data. (c) 2012 Wiley Periodicals, Inc. J Appl Polym Sci, 2012
Keywords: mechanical properties; miscibility; modification; polymer blends

Overview on the cellulose based conducting composites - Pandey, Jitendra Kumar; Takagi, Hitoshi; Nakagaito, Antonio Norio; Saini, Daulat Ram; Ahn, Sung-Hoon (Composites Part B-Engineering, 2012)
Biopolymer based composites have been employed in numerous applications with increasing interest not only due to renewable, eco-friendly nature, but also because of the flexibility in processing conditions and competitive cost of their end products. The conductive materials from biopolymers have been found applicable in robots, medical imaging, sensitive membranes, actuators, visual displays, electronic wiring and shielding, and components in batteries. Cellulose is one of the most abundant biopolymers in the nature, which has received special attention for development of conducting materials due to biocompatibility for protein and drug immobilization and ability to form the composites with synthetic polymers. The present review is aimed to provide concisely the current status in this field of conducting composites from cellulose, with brief discussions of associated problems and future applications. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Fibres; mechanical properties; Nano-structures; Polymer-matrix composites (PMCs)

Effect of organic modification on the intercalation and the properties of poly(phenylene oxide)/polystyrene blend-clay nanocomposites - Tiwari, Rajkiran R.; Natarajan, Upendra (Journal of Thermoplastic Composite Materials, 2013)
Nanocomposites prepared by the dispersion of unmodified and organically modified montmorillonite (MMT) clay into poly(2,6-dimethyl phenylene oxide)/polystyrene miscible blend in the range of 2-10 wt% clay were investigated by wide-angle x-ray diffraction, transmission electron microscopy, differential scanning calorimetry, thermogravimetric analysis and tensile mechanical tests. The systems based on unmodified sodium MMT (Na+MMT) as well as Cloisite 20A, Cloisite 30B and Cloisite 10A organically modified clays showed polymer intercalation. The glass transition temperature (T-g) value was not affected by the volume fraction of clay and chemical nature of the organoclay. The thermal degradation stability of nanocomposites is found to be only slightly better than that of the blend matrix. A percolation threshold of around 4 wt% organoclay loading is observed. An improvement of 35% relative to unfilled polymer blend matrix is observed for the modulus, for Cloisite 20A nanocomposite containing 2 wt% organoclay. The observed modulus improvement with significant retention of elongational tensile strength and tensile ductility in case of unmodified Na-MMT and Cloisite 30B nanocomposites appears promising. The modulus prediction using Halpin-Tsai model is found to be closer to the experimental data when MMT volume fraction rather than the organoclay volume fraction is used.
Keywords: filler; interface; interphase; mechanical properties; Nanostructures; Polymer-matrix composites

Synergistic mechanical response of Nylon 6/Trogamid (R) T blends - Ridhore, Amol; Jog, Jyoti Prakash (Journal of Applied Polymer Science, 2013)
Blends of semicrystalline Nylon 6 with a varying ratios of amorphous Nylon are studied for their morphological, thermal, dielectric, and mechanical behavior. Thermal analysis indicated a compositional dependant decrease in the melting and crystallization temperatures of Nylon 6. The blends exhibited a single compositional dependant glass transition temperature in dynamic mechanical thermal analysis and dielectrical relaxation spectroscopy over entire mixing ratio indicating miscibility between the blend components. The values of flexural modulus and tensile modulus of the blends are found to increase without significant loss in the impact properties. The water absorption of the blends is also lower than the values calculated by rule of mixtures. The observed synergistic behavior of the mechanical properties of the blends is indicative of presence of strong interactions in the blends components. (c) 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013
Keywords: blends; dielectric properties; mechanical properties; polyamides; Thermal properties

Synthesis of novel silica-polyimide nanocomposite films using aromatic-amino modified silica nanoparticles: mechanical, thermal and morphological investigations - Ghorpade, Ravindra V.; Rajan, C. R.; Chavan, Nayaku; Ponrathnam, S. (Express Polymer Letters, 2015)
Silica nanoparticles were modified with aromatic amino groups and modified-silica/polyimide composite films were prepared using them. 3,3!, 4,4!-Benzophenone tetracarboxylic dianhydride (BTDA) and 4,4!-oxydianiline (ODA) were used as precursors for polyimide matrix. The structures of the modified nanoparticles and hybrid nanocomposites were identified using Fourier Transform Infrared (FTIR) spectrometry. The hybrid composite films were evaluated for mechanical, thermal and morphological characteristics. Morphological results describe a uniform dispersion of silica particles in the polymer matrix. The thermal stability and mechanical properties of polyimide composite were improved, and the decomposition temperature was increased when the amount of silica nanoparticles was increased.
Keywords: hybrid polyimide composites; mechanical properties; Nanocomposites; nanoparticle modification; Thermal properties

Synthesis and characterization of well-defined random and block copolymers of epsilon-caprolactone with l-lactide as an additive for toughening polylactide: Influence of the molecular architecture - Deokar, Megha D.; Idage, Susheela B.; Idage, Bhaskar B.; Sivaram, Swaminathan (Journal of Applied Polymer Science, 2016)
Well-defined multiarmed star random and block copolymers of epsilon-caprolactone with l-lactide with controlled molecular weights, low polydispersities, and precise numbers of arms were synthesized by the ring-opening polymerization of respective cyclic ester monomers. The polymers were characterized by H-1-NMR and C-13-NMR to determine their chemical composition, molecular structure, degree of randomness, and proof of block copolymer formation. Gel permeation chromatography was used to establish the degree of branching. Star-branched random copolymers exhibited lower glass-transition temperatures (T-g's) compared to a linear random copolymer. When the star random copolymers were melt-blended with poly(l-lactic acid) (PLA), we observed that the elongation of the blend increased with the number of arms of the copolymer. Six-armed block copolymers, which exhibited higher T-g's, caused the maximum improvement in elongation. In all cases, improvements in the elongation were achieved with no loss of stiffness in the PLA blends. (c) 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2016, 133, 43267.
Keywords: biodegradable; copolymers; differential scanning calorimetry; mechanical properties; ring-opening polymerization

Effect of electrostatic interactions on structure and mechanical properties of ice templated colloid-polymer composites - Suresh, Karthika; Kumaraswamy, Guruswamy (Journal of Physics D-Applied Physics, 2019)
When an aqueous dispersion of negatively charged colloids, cationic polymer and crosslinker is frozen and the polymer is allowed to crosslink in the frozen state, we obtain a self-standing macroporous composite foam. This material is soft, despite the high concentration of colloids and yet is remarkably elastic to large compressive strains. In these macroporous composites, the pore walls comprise colloidal particles held within a crosslinked polymer network. Here, we investigate the effect of varying colloid- polymer interactions in pre-fabricated macroporous composites on their microstructure and mechanical properties. During preparation of the composite, cationic polymer adsorbs on the negatively charged colloids. We tune the surface charge of particles embedded in a macroscopic monolith by immersing the composites in water maintained at different pH. In this way, we tune polymer-particle interactions in the composite. We observe a sudden increase in interparticle distance and swelling of composite when pH is decreased below the particle's isoelectric point. Correspondingly, we observe reduction in Young's and shear moduli, compression strength and macroscopic energy dissipation. We did not observe any pH dependent changes in pure polymer sponges (prepared by ice templating and crosslinking a polymer solution that does not contain colloidal particles). Therefore, the pH dependent structural and mechanical property changes arise from the composite structure rather than purely from the crosslinked polymer. We believe that the reduction in mechanical stiffness when the polymer-particle interaction becomes repulsive is because of the reduction in interfacial contacts between particle and polymer. Therefore, the mechanical stiffness of ice templated composite is strongly influenced by interactions between the polymer and particle surface.
Keywords: colloid; electrostatic interaction; ice templating; mechanical properties; Polymer

Structure-property relations in regenerated cellulose fibers: comparison of fibers manufactured using viscose and lyocell processes - Sharma, Aakash; Nagarkar, Shailesh; Thakre, Shirish; Kumaraswamy, Guruswamy (Cellulose, 2019)
Regenerated cellulose fibers are produced using two industrially dominant technologies: the viscose and lyocell processes. Here, we compare commercially available fibers, prepared using the viscose and lyocell processes. Single fibers are subjected to a variety of mechanical deformations to obtain stress-strain, stress relaxation and stress recovery data. These are fitted to a phenomenological model, whose parameters are interpreted in terms of the fiber semicrystalline microstructure. This simple model does not incorporate the complexities of semicrystalline microstructure. Rather, it represents structure in a semicrystalline polymer fiber in terms of an elastic crystalline phase that coexists with a viscoelastic Voigt-like glassy amorphous phase. Lyocell fibers are characterized by higher values of crystalline modulus relative to viscose. Lyocell fibers also have a higher amorphous phase modulus and a wider relaxation spectrum than viscose, suggesting that amorphous and crystalline phases are dispersed in close connectivity in lyocell. Viscose and lyocell fibers exhibit qualitative similarities in their mechanical response. On stretching, there is a transition in the stress-strain curve from a low strain elastic response at a critical value of strain. This critical strain has been incorrectly attributed to yielding of the fiber. We establish that this critical value corresponds to an apparent yield. When subjected to strains higher than this apparent yield point, the fibers develop a memory of the mechanical deformation. This memory decays slowly, logarithmically with time and is lost over about a day as the fiber structure transitions back to the original as spun fiber. Finally, we demonstrate that on wetting the fibers with water, there is an increase in the apparent yield strain for viscose fibers, but not for lyocell. We interpret these results in terms of the semicrystalline microstructure of the fibers.
Keywords: mechanical properties; Model; Regenerated cellulose; Yielding

Critical organic modifier aliphatic tail length for the formation of poly(methyl methacrylate)-montmorillonite nanocomposites - Tiwari, Rajkiran R.; Natarajan, Upendra (Polymer Engineering and Science, 2020)
In this article, we report the influence of organic modifier structure (alkyl chain length C8-C20, single vs ditallow) and thereby, the effect of hydrophobicity on the structure, thermal and mechanical properties of poly(methyl methacrylate) (PMMA)-clay hybrids. Melt processed PMMA-clay hybrids were characterized using wide-angle X-ray diffraction, transmission electron microscopy, and differential scanning calorimetry. The organoclays having an alkyl chain length of more than 12 CH2 groups resulted in the formation of nanocomposites. The glass transition temperature (T-g) of PMMA increased in the presence of clay. The mean-field lattice model was used to predict the free energy for nanocomposite formation, which showed a reasonable match with the experimental results and provided a general guideline for the proper selection of polymer and organoclay (ie, organic modifier) to obtain nanocomposite. Tensile modulus showed maximum improvement of 58% for the nanocomposites compared to 9% improvement for the composites. Tensile modulus increased with increases in the alkyl chain length of the organic modifier and clay loading. The level of improvement for the tensile properties of nanocomposites prepared from primary and secondary ammonium-modified clay is the same as that obtained with the commercial organoclays.
Keywords: hybrid; mechanical properties; Montmorillonite; Nanocomposites; organoclay; poly(methyl methacrylate)

Piezoelectric energy harvesting from a ferroelectric hybrid salt [Ph3MeP](4)[Ni(NCS)(6)] embedded in a polymer matrix - Vijayakanth, Thangavel; Ram, Farsa; Praveenkumar, Balu; Shanmuganathan, Kadhiravan; Boomishankar, Ramamoorthy (Angewandte Chemie-International Edition, 2020)
Organic-inorganic hybrid ferroelectrics are an exciting class of molecular materials with promising applications in the area of energy and electronics. The synthesis, ferroelectric and piezoelectric energy harvesting behavior of a 3d metal ion-containing A(4)BX(6) type organic-inorganic hybrid salt [Ph3MeP](4)[Ni(NCS)(6)] (1) is now presented. P-E hysteresis loop studies on 1 show a remnant ferroelectric polarization value of 18.71 mu C cm(-2), at room temperature. Composite thermoplastic polyurethane (TPU) devices with 5, 10, 15 and 20 wt % compositions of 1 were prepared and employed for piezoelectric energy harvesting studies. A maximum output voltage of 19.29 V and a calculated power density value of 2.51 mW cm(-3) were observed for the 15 wt % 1-TPU device. The capacitor charging experiments on the 15 wt % 1-TPU composite device shows an excellent energy storage performance with the highest stored energies and measured charges of 198.8 mu J and 600 mu C, respectively.
Keywords: energy conversion; mechanical properties; non-covalent interactions; organic-inorganic hybrid composites; Phosphorus

Study of interfacial adhesion between nickel-titanium shape memory alloy and a polymer matrix by laser surface pattern - Samal, Sneha; Tyc, Ondrej; Heller, Ludek; Sittner, Petr; Malik, Monika; Poddar, Pankaj; Catauro, Michelina; Blanco, Ignazio (Applied Sciences-Basel, 2020)
The aim of this article is to investigate the interfacial adhesion of Ni-Ti shape memory alloy with a polymer matrix of Poly (methyl methacrylate) (PMMA). The surface pattern on Ni-Ti plates was channeled by a solid state laser machine. The laser machine allows for creating channels on the Ni-Ti surface for infiltration of the PMMA matrix, which could be attached as an intra-surface locking pattern to the Ni-Ti surface. The influence of the PMMA matrix on the surface of the NiTi plate was evaluated by thermomechanical analysis (TMA) and dynamic mechanical analysis (DMA). The surface characterization was carried out by an optical microscope on the PMMA/NiTi composite after mechanical testing. During mechanical testing, the polymer displays the multiple cracks in the longitudinal direction that result in slipping and fracture. TMA and DMA analyses were performed on the Ni-Ti- and PMMA-coated Ni-Ti ribbon to observe elasticity and the storage modulus for both samples. Better adhesion than 80 % was observed in the Ni-Ti surface, in the laser surface pattern, in comparison to the free plain surface. However, the polymer acts as mechanical backing that caused a reduction in the shape-memory properties of the composite material.
Keywords: adhesion; mechanical properties; NiTi composites; NiTi plate; PMMA; Polymer; surface features

Mechanical properties of anodic titanium dioxide nanostructures - Kulkarni, Mukta; Sepitka, Josef; Junkar, Ita; Bencina, Metka; Rawat, Niharika; Mazare, Anca; Rode, Chandrashekhar; Gokhale, Suresh; Schmuki, Patrik; Daniel, Matej; Iglic, Ales (Materiali in Tehnologije, 2021)
Highly ordered and uniform titanium dioxide (TiO2) nanotubes (NTs) with different morphologies (15 nm, 50 nm and 100 nm in diameter) were prepared by the electrochemical anodization of Ti substrates. The TiO2 NTs' surface properties were characterized by X-ray diffraction (XRD) spectroscopy, Raman spectroscopy, scanning electron microscopy (SEM) and atomic force microscopy (AFM). The elastic modulus (E) and the Vickers hardness (HV) of the Ti foil and of the different-morphology TiO2 NTs were evaluated with the nano-indentation technique. E and HV increase with the decreasing length/diameter of the NTs, meaning that NTs with smaller diameters are more resistant to mechanical wear. The elastic modulus of the TiO2 NTs with 15-nm and 50-nm diameters is similar to that of the human bone.
Keywords: Elastic modulus; mechanical properties; titanium dioxide (TiO2) nanotubes; Vickers hardness

Structure-property correlation of halogen substituted benzothiazole crystals - Thekkeppat, Nipun P.; Singla, Labhini; Tothadi, Srinu; Das, Priyadip; Choudhury, Angshuman Roy; Ghosh, Soumyajit (Journal of Molecular Structure, 2021)
We have synthesized 3 benzothiazole crystals (1-3) based on existing knowledge of combining flexibility and optical properties towards achieving applications for flexible optoelectronics. However, one crystal was found to be elastically bendable and was found to comply necessary packing features for elasticity. Other two crystals do not obey packing features for elasticity hence they are brittle in nature. Further, Hirshfeld analysis illustrates that elastic crystal 1 possess more number of weak and dispersive interactions compared to other crystals. These interactions were instrumental in invoking elasticity. Moreover, crystals 1-3 were found to be fluorescent as well at specific excitation wavelengths. Therefore, among these crystals, particularly crystal 1 is considered as more promising candidate for flexible optoelectronics. (C) 2021 Elsevier B.V. All rights reserved.
Keywords: Benzothiazole crystals; Elasticity; Halogen bond; mechanical properties

Different mechanical responses of dimorphic forms of anthracene schiffbase crystal - Lakshmipathi, Madhumathi; Tothadi, Srinu; Emmerling, Franziska; Bhattacharya, Biswajit; Ghosh, Soumyajit (Journal of Molecular Structure, 2022)
We obtained concomitant dimorphic forms of Anthracene Schiffbase (N-(anthracen-9-yl methylene)-2,5dichloroaniline) from hexane solvent. Two polymorphs can be differentiated by their morphology and mechanical properties. One form is long acicular type and elastically bendable while another form is block shaped and brittle in nature. Mechanical property is attributed to underlying crystal packing. Hirshfeld analysis and energy framework calculations were done to corroborate structure-property correlation of two forms (C) 2021 Elsevier B.V. All rights reserved.
Keywords: Anthracene schiffbase; Dimorphs; Elasticity; mechanical properties

Study on anisotropy in wire arc additively manufactured Inconel 625 multi-layered wall and its correlation with molten pool thermal history - Nagallapati, Vishwanath; Choudhary, Amit; Torris, Arun; Muvvala, Gopinath; Dadasaheb, Sagar Pawar; Gudur, Srinath Ellaswamy (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2022)
In the present study, the variation in molten pool thermal history with layer number during wire arc additive manufacturing of Inconel 625 wall was investigated. Further, its effect on the evolution of microstructure and anisotropy in mechanical and corrosion properties was reported. During the deposition process, the molten pool thermal history was monitored using a non-contact type IR pyrometer operating at 1.6 mu m wavelength. A total number of 40 layers were deposited, building a wall of 60 mm height. With an increase in layer number, the molten pool lifetime and cooling rate were found to increase and decrease, respectively, resulting in coarse grains and increased elemental segregation or Laves phase formation. To investigate its effect on mechanical properties, the samples were collected in a skewed fashion along the height with orientation in the deposition direction. The tensile specimens collected close to the substrate exhibited better strength and ductility, while the samples from the top location of the wall exhibited a relatively brittle mode of fracture, which was investigated by carrying out the fracture surface analysis using SEM. Corrosion test was also conducted along the height of the wall, wherein the samples close to substrate exhibited better corrosion resistance due to refined microstructure and low elemental segregations. Further, EDS, XRD analysis and hardness test were carried out to investigate the elemental composition, variation in phases and hardness with layer number, respectively.
Keywords: anisotropy; Layer number; mechanical properties; Molten pool thermal history; Wire arc additive manufacturing

Electronic, magnetic, and mechanical properties of co-doped GaSb: A promising diluted magnetic semiconductor - Samant, Ramnath; Saraf, Deepashri; Adhikari, Rajendra P.; Shilkar, Omkar; Raikar, Sakshit; Silveira, Allan; Sawant, Manthan; Sappati, Subrahmanyam; Joshi, Niharika; Desai, Ashish M. (Journal of Magnetism and Magnetic Materials, 2025)
{Understanding the interplay between magnetism and the electronic structure is crucial for the development of novel spintronic materials. This study employs density functional theory (DFT) calculations to investigate these properties in cubic Gallium Antimonide (GaSb) doped with Cobalt (Co) (Ga1-xCoxSb
Keywords: Density functional theory; Dilute magnetic semiconductors; Electronic properties; GaSb; mechanical properties; Spintronic materials

Enhancement of mechanical and rheological properties of PA-12 through silane modification - Jadhav, V. Pravin; Mahajan, Digvijay; Patil, Prashant; Umbarkar, Shubhangi B.; Pol, Harshawardhan (Bulletin of Materials Science, 2025)
This research examines the effects of silane modifications on polyamide 12 (PA-12) to improve its mechanical and thermal properties. The study employs a reactive extrusion technique to integrate various silanes-Dynasylan (R) AMEO, Dynasylan (R) 1189, Dynasylan (R) DAMO and Dynasylan (R) VPS 4721-at different concentrations (0.25, 0.5 and 0.75%). Key findings reveal that silane modifications significantly enhance the tensile strength, impact resistance and viscoelastic behaviour of PA-12, with the Dynasylan (R) DAMO formulation achieving the highest tensile strength of 38.25 MPa vis-& agrave;-vis 8.02 MPa for PA-12. The modifications also resulted in a reduction of crystallinity by over 35%, contributing to improved toughness and impact strength. Rheological assessments indicate that the flow properties of PA-12 are positively altered, enhancing its complex viscosity and storage modulus, which are crucial for applications in automotive and aerospace industries. Thermal analysis through differential scanning calorimetry and thermogravimetric analysis confirms improved thermal stability, particularly in the 0.5% Dynasylan (R) AMEO-modified sample, exhibiting an onset temperature of 421.87 degrees C. The study emphasizes the importance of the silane type and dosage in tailoring PA-12's performance for advanced applications, suggesting future research directions to further refine silane-modification techniques for enhanced polymer performance. This research provides valuable insights into polymer-modification strategies, highlighting the potential for silane treatments to optimize the mechanical, thermal and rheological properties of PA-12 for diverse industrial applications.
Keywords: mechanical properties; Polyamide 12 (PA-12); reactive extrusion; rheological behaviour; silane modification; thermal stability